Surfactant-enhanced bioremediation of n-hexadecane-contaminated soil using halo-tolerant bacteria Paenibacillus glucanolyticus sp. strain T7-AHV isolated from marine environment - Ghafari, Shokouh (Array, 2019)
A halo-tolerant bacterial strain Paenibacillus glucanolyticus sp. strain T7-AHV isolated from marine environment was used for bioremediation of n-hexadecane-contaminated soil. Soil/water ratio, initial inoculums volume, surfactant addition, n-hexadecane concentration, and salinity were investigated. The possibility of biosurfactant production by isolated strain was also studied, and the results demonstrated that it was not a biosurfactant producer, based on measurement of the surface tension of culture broth. Both tween 80 and rhamnolipid enhanced the biodegradation of n-hexadecane significantly up to 44 and 46 %, respectively. A biodegradation rate of 39.7 % was observed at salinity level of up to 2 %, and the biodegradation efficiency decreased significantly at higher salinity concentrations. A natural hydrocarbon-contaminated soil sample with total petroleum hydrocarbon (TPH) concentration of 1437 mg kg–1 was subjected to bioremediation using the selected conditions of operational parameters, and a biodegradation rate of 22.1 % was obtained.